Sistem Informasi Arus Kas pada Credo Union Modifikasi (CUM) Talenta Saribu Dolok Berbasis Web - Mira Naftalia Sijabat; Resianta Perangin-angin; Rena Nainggolan (Universitas Methodist Indonesia, 2024)
The data that has not been input is directly stored in the database. I have not been able to make online payments via bank transfer to Talenta because the commissioner and teller cannot be connected between accounts. The purpose of this is to produce a cash flow information system. Method of direct observation in more depth on an object to obtain more detailed and accurate information and Literature study is the process of collecting information from reliable readings or sources such as articles, books and scientific journals on topics related to the creation of website pages and databases. Able to input Member/Credit Customer Deposits. Confirm the bank transfer payment proof from the member. adding expenses in the office. Can view the account data used on Talenta. Adding Members, Credit Customers, and Employees. Input member deposits, credit deposits, Proof of Transfer, Payment Confirmation and Expenses in the office. View Member reports, Employee data reports, Member deposit reports, Member credit deposit reports, and Cash Flow statements. Conclusion The system can upload proof of payment that has been transferred by customer members to the Talenta account through the commissioner in the field. It can help and facilitate employees in inputting data on members, employees, member deposits, credit customers, and expenses. The information system built can present the required reports.